The long-term outcomes of recurrent adhesive small bowel obstruction after colorectal cancer surgery favor surgical management. Issue 43 (October 2017) - Yang, Kwan Mo; Yu, Chang Sik; Lee, Jong Lyul; Kim, Chan Wook; Yoon, Yong Sik; Park, In Ja; Lim, Seok-Byung; Kim, Jin Cheon
Abstract : Abstract: An adhesive small bowel obstruction (ASBO) is generally caused by postoperative adhesions and is more frequently associated with colorectal surgeries than other procedures. We compared the outcomes of operative and conservative management of ASBO after primary colorectal cancer surgery. We retrospectively reviewed 5060 patients who underwent curative surgery for primary colorectal cancer; 388 of these patients (7.7%) were readmitted with a diagnosis of SBO. We analyzed the clinical course of these patients with reference to the cause of their surgery. Of the 388 SBO patients analyzed, 170 were diagnosed with ASBO. Their 3-, 5-, and 7-year recurrence-free survival rates were 86.1%, 72.8%, and 61.5%, respectively. The median follow-up period was 59.2 months. Repeated conservative management for ASBO without surgical management led to higher recurrence rates: 21.0% after the first admission, 41.7% after the second, 60.0% after the third, and 100% after the fourth ( P = .006). Surgical management was needed for 19.2%, 22.2%, 50%, and 66.7% of patients admitted with ASBO on the first to fourth hospitalizations, respectively. Repeated hospitalization for obstruction led to a greater possibility of surgical management ( P = .001). Of 27 patients with surgical management at the first admission, 6 (17.6%) were readmitted with a diagnosis of SBO, but there were no further episodes of SBO in the surgically managed patients. Patients who undergo operative management for ASBO have a reduced risk of recurrence requiring hospitalization, whereas those with repeated conservative management have an increased risk of recurrence and require operative management. Operative management should be considered for recurrent SBO. Abstract : Supplemental Digital Content is available in the text